The sociopsychological conception of law in Pontes de Miranda’s Philosophy (Research, Society and Development, 2025)
This study aims to provide brief considerations on the sociopsychological conception of law in Pontes de Miranda’s work, highlighting his pioneering role in overcoming the dichotomy between objectivism (social structures) and subjectivism (individual representations). Traditional legal theory associates law with the State and codified norms, whereas Pontes de Miranda understands it as a process of social adaptation and a product of psychic assimilation and dissimilation. Methodologically, this research is bibliographic in nature, seeking works on the subject and conducting a critical and dialogical reading of the found materials. The results demonstrate that, in Pontes de Miranda’s view, law is a natural phenomenon essential to social life, not limited to state legislation but rooted in social practices. It consists of an internal criterion of valuation, a system of evaluating or measuring facts, ingrained in individuals throughout their lives in society.